Frozen section in thyroid gland follicular neoplasms: It's high time to abandon it!. (March 2021) - Sanabria, Alvaro; Zafereo, Mark; Thompson, Lester D.R.; Hernandez-Prera, Juan C.; Kowalski, Luiz P.; Nixon, Iain J.; Shaha, Ashok; Rodrigo, Juan P.; Mäkitie, Antti; Poorten, Vincent Vander; Suarez, Carlos; Zbären, Peter; et al.
Abstract: Thyroid nodules are a very common clinical condition. The 2015 American Thyroid Association (ATA) guidelines recommend surgical excision for Bethesda IV nodules. The use of intraoperative frozen section (FS) has been recommended as a strategy to tailor the extent of the initial surgery. We critically evaluated the literature that discusses the utility and cost-effectiveness of FS to make an intraoperative decision in patients with thyroid nodules classified as follicular neoplasm. FS should not be recommended as a routine intraoperative test to assess for malignancy in thyroid follicular patterned lesions due to its low performance; the high number of deferred results; the inability to adequately assess histologically defining features; the improvements in risk stratification guiding total thyroidectomy; and the low cost-effectiveness of FS. Highlights: Frozen section has been recommended in the diagnosis of a thyroid follicular neoplasia. Frozen section performance is poor for thyroid follicular neoplasms. Frozen section should not be recommended as a test to assess malignancy in thyroid follicular lesions.